TNF is a potential therapeutic target to suppress prostatic inflammation and hyperplasia in autoimmune disease - Renee E. Vickman; LaTayia Aaron-Brooks; Renyuan Zhang; Nadia A. Lanman; Brittany Lapin; Victoria Gil; Max Greenberg; Takeshi Sasaki; Gregory M. Cresswell; Meaghan M. Broman; J. Sebastian Paez; Jacqueline Petkewicz; et al. (Nature Communications, 2022)
Reduction of systemic autoimmunity using TNF blockers may also reduce inflammatory diseases in other organs. Here, the authors use a patient database and scRNA-seq to link autoimmune diseases to benign prostatic hyperplasia (BPH), and demonstrate that prostatic hyperplasia is reduced by TNF blockers in humans and mice.